Crack-free magnesium alloy surface chemical conversion coating with self-repairing property and preparation method thereof

By forming a vanadium-rich composite salt film layer without cracks and self-repairability on the surface of the magnesium alloy, the problem of insufficient corrosion resistance of the magnesium alloy in a corrosive environment is solved, and the high corrosion resistance and self-repairability on the surface of the magnesium alloy is achieved, which improves its service life and safety.

CN119640247APending Publication Date: 2025-03-18BAOSTEEL METAL CO LTD +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202311200394.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-18
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Magnesium alloys are prone to galvanic corrosion and environmental corrosion in corrosive environments, resulting in insufficient corrosion resistance and limiting their widespread application.

Method used

A chemical conversion film with no cracks and self-healing properties is formed on the surface of the magnesium alloy. A vanadium-rich composite salt film layer composed of magnesium, phosphorus, calcium, vanadium, etc. is used to form a uniform and dense film layer through passivation and sealing treatment, which has self-healing properties.

Benefits of technology

It improves the corrosion resistance and service life of magnesium alloy, avoids the harm of traditional chromium-containing self-repairing films to the environment and the human body, and is simple to operate and has strong applicability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640247A_ABST
    Figure CN119640247A_ABST
Patent Text Reader

Abstract

The invention relates to a crack-free magnesium alloy surface chemical conversion coating with self-repairing property and a preparation method thereof. The chemical conversion coating comprises the following components in percentage by weight: 10.0-30.0% of Mg, 0-5% of Al, 60-75% of V, 1-7% of P, 1-3% of Ca, 1-2% of Si, 1-5% of O and the balance of impurities. The formed chemical conversion coating does not contain elements such as chromium harmful to the environment and human bodies, has self-repairing performance, is uniform, compact and crack-free, improves the corrosion resistance of the magnesium alloy, prolongs the service life of the magnesium alloy, and is simple in operation method and high in applicability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of magnesium alloy surface treatment, and in particular to a magnesium alloy surface chemical conversion film which is crack-free and self-repairing and a preparation method thereof. Background Art

[0002] Magnesium alloy has low density and high specific strength, and is currently the most ideal lightweight and high-strength structural material. As a green engineering material in the 21st century, magnesium alloy is widely used in aerospace, automobile, 3C products, medical and other fields due to its many advantages. However, magnesium and its alloys have the lowest standard electrode potential among metal structural materials. The conversion film formed under natural conditions is not dense enough to play a protective role. In most corrosive environments, galvanic corrosion and environmental corrosion are prone to occur, and it cannot be used continuously for a long time. This defect seriously limits the widespread application of magnesium alloys.

[0003] At present, improving the corrosion resistance of magnesium alloys by surface treatment is one of the most effective means to promote the industrial application of magnesium and its alloys, and important progress has been made in improving the corrosion resistance and application of magnesium alloys. However, magnesium alloys will inevitably be scratched or collided during engineering applications. Once the coating is damaged, corrosion will quickly spread along the damaged area into the magnesium matrix. Magnesium alloys cannot quickly re-passivate at the damaged coating to protect the matrix like aluminum alloys and titanium alloys. On the contrary, magnesium alloys are prone to galvanic corrosion, which poses a great threat to the safety of component use. If the damaged area is not quickly protected or repaired, it will affect the service life and safety of the product.

[0004] Based on the above problems, a layer of self-healing chemical conversion film is prepared on the surface of the magnesium alloy as the bottom layer in direct contact with the magnesium alloy. Once the magnesium alloy substrate is scratched, the film layer will spontaneously repair the damaged area, thereby protecting the magnesium alloy substrate from erosion by corrosive media, thereby achieving the purpose of improving the corrosion resistance and service life of the magnesium alloy product.

[0005] Chinese patent CN108300255B discloses "a self-repairing coating formed on the surface of a magnesium alloy and a method for forming a self-repairing coating", Chinese patent CN112962090A discloses "a self-repairing chromium-free passivator for zinc-aluminum-magnesium alloy, its preparation method and application", and Chinese patent CN115738938A discloses "microcapsules for self-repairing anti-corrosion coating of magnesium alloy, its preparation method and self-repairing anti-corrosion coating". The above patents all disclose how to form an organic paint film on the surface of a magnesium alloy. The organic paint film is in direct contact with the magnesium alloy substrate, and there is a problem of weak bonding between the paint film and the substrate. In addition, for complex magnesium alloy structural parts, it is impossible to ensure uniform coverage of the surface of the magnesium alloy substrate.

[0006] Chinese patent CN112941497A discloses "a method for preparing a rapid self-repairing system based on a magnesium alloy protective layer", Chinese patent CN109680319B discloses "a method for preparing a corrosion-resistant self-repairing coating on the surface of a magnesium alloy based on calcium salt", and Chinese patent CN109680318B discloses "a method for preparing a corrosion-resistant self-repairing coating on the surface of a magnesium alloy based on phosphate". The above self-repairing coatings on the surface of magnesium alloys are all based on the modification of the existing plating layer and micro-arc oxidation layer by the self-repairing coating to achieve self-repairability, but the operation is cumbersome and the cost is high, which is not conducive to actual mass production.

[0007] Chinese patent CN109402621A discloses "a film-forming solution and film preparation method for a chromium-free and crack-free conversion film of a magnesium alloy", which describes a method for preparing a crack-free conversion film on the surface of a magnesium alloy. However, the chemical conversion film prepared by this technology has no self-healing properties, and the corrosion resistance of the unstacked structure of the coating is limited.

[0008] From the existing technology, in order to make the magnesium alloy surface coating have self-repairing ability, it is usually achieved by using organic paint film or micro-arc oxidation. Alternatively, chromate passivation treatment is used to form a chromium-containing self-repairing passivation film on the surface. However, since Cr (VI) is harmful to the environment and human body, the use of chromate is strictly restricted at home and abroad. Summary of the invention

[0009] The purpose of the present invention is to provide a crack-free and self-healing magnesium alloy surface chemical conversion film and a preparation method thereof. The formed chemical conversion film does not contain chromium and other elements harmful to the environment and human body, and has self-healing properties. The film layer is uniform and dense without cracks, thereby improving the corrosion resistance and service life of the magnesium alloy.

[0010] To achieve the above object, the technical solution of the present invention is:

[0011] A crack-free and self-repairing magnesium alloy surface chemical conversion film, the components of which are as follows by weight: Mg: 10.0-30.0%, Al: 0-5%, V: 60-75%, P: 1-7%, Ca: 1-3%, Si: 1-2%, O: 1-5%, and the remainder is impurities.

[0012] The chemical conversion film formed on the surface of the magnesium alloy in the present invention is a vanadium-rich composite salt film layer composed of magnesium, phosphorus, calcium, vanadium and the like.

[0013] During the engineering application process, magnesium alloy is scratched or collided, and the vanadium-rich composite salt film layer is damaged, exposing the magnesium alloy matrix. Once the magnesium alloy matrix reacts with water, resulting in an increase in the local pH value, the vanadium-rich composite salt film layer will replace the magnesium alloy matrix in the damaged area to react with water to form a new protective film, thereby improving the integrity of the chemical conversion film and playing a role in blocking and buffering the magnesium alloy matrix. At the same time, the vanadium-rich composite salt film layer can also hinder further erosion by chloride ions, improve the corrosion resistance of the damaged area, prevent further or diffuse corrosion in the damaged area, and prevent the corrosive liquid from corroding the magnesium alloy matrix, thereby further improving the corrosion resistance and service life of the magnesium alloy.

[0014] The present invention also provides a method for preparing a crack-free and self-repairing magnesium alloy surface chemical conversion film, comprising the following steps:

[0015] 1) Pre-treatment

[0016] The magnesium alloy substrate is successively polished, alkali washed, pickled, bleached and deashed;

[0017] 2) Passivation

[0018] The pre-treated magnesium alloy substrate is placed in a passivation solution for passivation treatment at a temperature of 15 to 40°C for a passivation treatment time of 0.5 to 3 minutes;

[0019] The passivation solution comprises the following components in concentrations: 1.0-10.0wt.% phosphoric acid, 1.0-40.0wt.% dihydrogen phosphate, 1.0-20.0wt.% calcium nitrate, 5.0-30.0wt.% metavanadate, 0.01-1wt.% complexing agent, 0.01-1wt.% surfactant, 0.01-1wt.% corrosion inhibitor, and the balance is water;

[0020] 3) Closed treatment

[0021] The magnesium alloy substrate is placed in a sealing solution for sealing treatment, the sealing treatment temperature is 50 to 90° C., and the sealing treatment time is 0.5 to 10 minutes;

[0022] The sealing solution comprises the following components: 10.0-30.0wt% metavanadate, 1.0-30.0wt% aminosilane, 1.0-20.0wt% nano silica sol, 0.01-1wt% complexing agent, 0.01-1wt% surfactant, 0.01-1wt% corrosion inhibitor, and the balance is water.

[0023] Preferably, in step 1), the alkali washing temperature is 50-80° C., and the alkali washing time is 5-20 min; preferably, the solution used for alkali washing comprises: 1.0-20.0 wt. % of sodium hydroxide, 1.0-20.0 wt. % of sodium phosphate, 1.0-30.0 wt. % of sodium carbonate, 0.01-1 wt. % of a surfactant, and the balance is water.

[0024] Preferably, in step 1), the pickling temperature is 15-70°C, and the pickling time is 0.5-3 min; preferably, the solution used for pickling comprises: 1.0-30.0wt.% oxalic acid, 1.0-30.0wt.% lactic acid, 1.0-30.0wt.% citric acid, 1.0-30wt.% glycolic acid, 0.01-1wt.% surfactant, and the balance is water.

[0025] Preferably, in step 1), the bleaching and deashing temperature is 60-90° C., and the bleaching and deashing time is 0.5-10 min; preferably, the solution used for bleaching and deashing comprises: 1.0-20.0 wt. % of sodium hydroxide, 1.0-30.0 wt. % of disodium ethylenediaminetetraacetate, 1.0-30.0 wt. % of sodium carbonate, 1-10.0 wt. % of triethanolamine, 0.01-1 wt. % of a surfactant, and the balance is water.

[0026] Preferably, the complexing agent is one or more of citric acid, succinic acid, EDTA, and ethylenediamine.

[0027] Preferably, the corrosion inhibitor is one or more of the anode corrosion inhibitor vanadate, the cathode corrosion inhibitor phosphate, the organic corrosion inhibitor phosphine carboxylic acid, phosphonate and the like.

[0028] Preferably, the surfactant is an anionic surfactant, a cationic surfactant, a zwitterionic surfactant and a nonionic surfactant.

[0029] Preferably, the magnesium alloy substrate is rinsed with deionized water 1 to 2 times after the grinding, alkali washing, pickling, bleaching and deashing, and passivation steps.

[0030] In the preparation method of the present invention:

[0031] The purpose of the alkali washing of the present invention is to remove the release agent, oil stains, etc. on the surface of the magnesium alloy. The purpose of the pickling is to remove the oxides on the surface of the magnesium alloy substrate. The purpose of the bleaching and deashing is to remove the pickling products attached to the magnesium alloy after pickling, and at the same time, the second phase on the surface of the substrate can be removed, so that the surface of the magnesium alloy forms a uniform phase, which is conducive to the subsequent passivation to form a dense conversion film.

[0032] The purpose of passivation is to react the magnesium alloy matrix with the solution to form a conversion film, thereby improving the corrosion resistance of the magnesium alloy. The passivation solution used in the present invention is based on the original phosphating solution, and 5.0-30.0wt.% metavanadate is added, wherein the α-Mg phase on the surface of the magnesium alloy matrix reacts with the passivation solution to form a basic film layer, and the matrix β phase reacts with the passivation solution to form irregular particles composed of magnesium, phosphorus, calcium, vanadium, etc. attached to the basic film layer, and finally a vanadium-rich composite salt film layer is formed on the surface of the magnesium alloy matrix, which has a certain self-repairing property.

[0033] After the passivation treatment, there may still be some cracks on the surface of the conversion film. The present invention further performs a sealing treatment. The presence of metavanadate, silane, silica sol and chelating agent in the sealing solution will react with the magnesium alloy matrix through the cracks and fill in the structure of the vanadium-rich composite salt film layer, thereby making the final chemical conversion film layer more complete and improving the integrity, corrosion resistance and self-repairing properties of the chemical conversion film. Compared with other chemical conversion films, especially magnesium alloy phosphating films and their phosphating processes, the problem of microscopic cracks on the surface of the chemical film layer is solved, the corrosion resistance of the magnesium alloy surface is improved, and the chemical film layer has a certain self-repairing ability.

[0034] A self-repairing passivation solution for magnesium alloy surface treatment comprises the following components: 1.0-10.0wt.% phosphoric acid, 1.0-40.0wt.% dihydrogen phosphate, 1.0-20.0wt.% calcium nitrate, 5.0-30.0wt.% metavanadate, 0.01-1wt.% complexing agent, 0.01-1wt.% surfactant, 0.01-1wt.% corrosion inhibitor, and the balance is water.

[0035] A self-repairing sealing solution for magnesium alloy surface treatment comprises the following components: 10.0-30.0wt.% metavanadate, 1.0-30.0wt.% aminosilane, 1.0-20.0wt.% nano silica sol, 0.01-1wt.% complexing agent, 0.01-1wt.% surfactant, 0.01-1wt.% corrosion inhibitor, and the balance is water.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] The chemical conversion film formed on the surface of the magnesium alloy in the present invention is a vanadium-rich composite salt film composed of magnesium, phosphorus, calcium, vanadium, etc. Once the film is damaged and the magnesium alloy substrate is exposed, the vanadium-rich composite salt film in the damaged area will replace the magnesium alloy substrate and react with water to generate a new film, which plays a role in repairing the damaged area, so that the formed chemical conversion film has self-repairing properties. Compared with the traditional chromium-containing self-repairing passivation film, the use of toxic and harmful elements chromium is reduced.

[0038] The present invention adopts a passivation + sealing treatment process to avoid the presence of cracks on the surface of the passivation treatment alone, thereby improving the compactness of the chemical conversion film, thereby forming a complete crack-free self-repairing chemical conversion film on the surface of the magnesium alloy substrate.

[0039] Compared with the conventional method of obtaining a self-repairing coating by using an organic paint film or micro-arc oxidation, the method of the present invention for obtaining a chemical conversion film with self-repairing ability directly reacts a magnesium alloy substrate with a solution to form an inorganic composite film layer, and the operation method is simple and has strong applicability.

[0040] The passivation solution used in the present invention is based on the original phosphating solution, and metavanadate is added. The α-Mg phase on the surface of the magnesium alloy substrate reacts with the passivation solution to form a basic film layer, and the β phase of the substrate reacts with the passivation solution to form irregular particles composed of magnesium, phosphorus, calcium, vanadium, etc., which are attached to the basic film layer, and finally form a vanadium-rich composite salt film layer with self-repairing properties. Compared with the traditional phosphating solution, the formed chemical conversion film has self-repairing properties. Compared with the chromium-containing passivation solution, the use of toxic and harmful elements is avoided.

[0041] Metavanadate is also added to the sealing solution used in the present invention so as to be able to pass through cracks during the sealing process and form a crack-free film layer with a composition similar to that of the passivation film and mixed evenly. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 It is a process flow chart of the present invention.

[0043] Figure 2 This is a microscopic morphology photograph of the chemical conversion film layer prepared in Example 1 of the present invention.

[0044] Figure 3 This is a photograph of the appearance of the chemical conversion film prepared in Example 1 of the present invention after being subjected to a 100-hour neutral salt spray test.

[0045] Figure 4 This is a microscopic morphology photograph of the surface of the chemical conversion film layer prepared in Comparative Example 1.

[0046] Figure 5 This is a photograph of the appearance of the chemical conversion film prepared in Comparative Example 1 after a 100-hour neutral salt spray test.

[0047] Figure 6 This is a macroscopic photograph of the surface of the magnesium alloy with a chemical conversion film prepared in Example 2 of the present invention after the salt spray test.

[0048] Figure 7 This is a surface macroscopic photograph of the magnesium alloy with a chemical conversion film prepared in Example 2 of the present invention after being left to stand for 12 hours in a salt spray test. DETAILED DESCRIPTION

[0049] The technical solution of the present invention is described in detail below through examples. This example is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following examples.

[0050] Example 1

[0051] The sample to be processed is a 20mm×10mm×5mm AZ91D magnesium alloy substrate, and its chemical composition is as follows by mass percentage: Al: 8.5-9.5%, Zn: 0.45-0.90%, Mn: 0.17-0.40%, Si≤0.050%, Cu≤0.025%, Ni≤0.01, Fe≤0.004, and the remainder is Mg and unavoidable impurities.

[0052] The specific steps of preparing a crack-free and self-healing surface chemical conversion film on the sample surface are:

[0053] 1) Pre-treatment

[0054] The magnesium alloy substrate of the sample to be processed was successively polished, alkali washed, pickled, bleached and deashed;

[0055] The samples were polished with metallographic sandpaper to No. 2000, then cleaned with acetone, washed with ultrapure water, and dried;

[0056] The alkali washing temperature was 70°C, the alkali washing time was 15 min, and the sample was cleaned with ultrapure water after alkali washing. The alkali washing ingredients used were: 15wt.% sodium hydroxide, 5wt.% sodium phosphate, 10wt.% sodium carbonate, and 0.01wt.% Triton.

[0057] The pickling temperature is 25°C and the time is 3 minutes. After pickling, the sample is cleaned with ultrapure water. The composition of the pickling solution is: 10wt.% oxalic acid, 15wt.% lactic acid, 5wt.% citric acid, 1wt.% glycolic acid, 0.01wt.% sodium dodecyl sulfate, and the balance is water;

[0058] The bleaching and deashing temperature is 80°C and the time is 10 minutes. After bleaching and deashing, the sample is cleaned with ultrapure water. The bleaching and deashing solution comprises: 15wt.% sodium hydroxide, 20wt.% disodium ethylenediaminetetraacetic acid, 5wt.% sodium carbonate, 2wt.% triethanolamine, 0.1wt.% sodium dodecyl sulfate, and the balance is water.

[0059] 2) Passivation

[0060] The pre-treated magnesium alloy substrate was placed in a passivation solution for passivation treatment. The passivation temperature was 20°C and the treatment time was 1 min. After passivation, the sample surface was cleaned with ultrapure water.

[0061] The passivation solution comprises: 1wt.% phosphoric acid, 10wt.% dihydrogen phosphate, 20.0wt.% calcium nitrate, 30.0wt.% metavanadate, 0.1wt.% citric acid, 0.01wt.% sodium dodecyl sulfate, 1wt.% vanadate, and the balance is water;

[0062] 3) Closed treatment

[0063] The magnesium alloy substrate is placed in a sealing solution for sealing treatment, the sealing treatment temperature is 80°C, and the sealing treatment time is 8 minutes;

[0064] The sealing solution comprises components with the following concentrations: 20wt.% metavanadate, 10wt.% aminosilane, 1.0wt.% nano-silica sol, 1wt.% citric acid, 0.1wt.% Triton, 0.1wt.% phosphate, and the balance is water.

[0065] The element composition of the obtained chemical conversion film is: Mg: 16wt.%, Al: 3wt.%, V: 72wt.%, P: 5wt.%, Ca: 1wt.%, Si: 1wt.%, O: 2wt.%, and the remainder is impurities.

[0066] The microscopic morphology of the chemical conversion film obtained on the sample surface is shown in Figure 2 As shown in Figure 2, a dense chemical conversion film is formed on the surface of the magnesium alloy substrate.

[0067] The chemical conversion film prepared in Example 1 was subjected to a 100-hour neutral salt spray scratch test. Figure 3 This is a photo of the appearance after a 100-hour neutral salt spray test. It can be seen that there are no corrosion spots in the unscratched area of ​​the surface and in the scratched and nearby areas.

[0068] Example 2

[0069] The sample to be processed is an AM60B magnesium alloy substrate of 20mm×10mm×5mm, and its chemical composition is as follows by mass percentage: Al: 5.5-6.4%, Zn: 0.30%, Mn: 0.24-0.60%, Si: 0.08%, Cu≤0.025%, Ni≤0.01, Fe≤0.004, and the remainder is Mg and unavoidable impurities.

[0070] The specific steps of preparing a crack-free and self-healing surface chemical conversion film on the sample surface are:

[0071] 1) Pre-treatment

[0072] The magnesium alloy substrate of the sample to be processed was successively polished, alkali washed, pickled, bleached and deashed;

[0073] The samples were polished with metallographic sandpaper to No. 2000, then cleaned with acetone, washed with ultrapure water, and dried;

[0074] The alkali washing temperature is 65°C, the alkali washing time is 20 minutes, and the sample is cleaned with ultrapure water after alkali washing. The alkali washing ingredients used are: 10wt.% sodium hydroxide, 10wt.% sodium phosphate, 5wt.% sodium carbonate, and 0.1wt.% hexadecyltrimethylammonium bromide;

[0075] The pickling temperature is 70°C and the time is 0.5 min. After pickling, the sample is cleaned with ultrapure water. The composition of the pickling solution is: 10wt.% oxalic acid, 15wt.% lactic acid, 5wt.% citric acid, 1wt.% glycolic acid, 0.01wt.% hexadecyltrimethylammonium bromide, and the balance is water;

[0076] The bleaching and deashing temperature is 70°C and the time is 15 minutes. After bleaching and deashing, the sample is cleaned with ultrapure water. The bleaching and deashing solution comprises: 20wt.% sodium hydroxide, 15wt.% disodium ethylenediaminetetraacetic acid, 10wt.% sodium carbonate, 5wt.% triethanolamine, 0.1wt.% Triton, and the balance is water.

[0077] 2) Passivation

[0078] The pre-treated magnesium alloy substrate was placed in a passivation solution for passivation treatment at a temperature of 15°C for 5 minutes. After passivation, the surface of the sample was cleaned with ultrapure water.

[0079] The passivation solution comprises: 2wt.% phosphoric acid, 40wt.% dihydrogen phosphate, 1.0wt.% calcium nitrate, 5.0wt.% metavanadate, 1wt.% succinic acid, 0.1wt.% Triton, 1wt.% vanadate, and the balance is water;

[0080] 3) Closed treatment

[0081] Then, the magnesium alloy substrate is placed in a sealing solution for sealing treatment, the sealing treatment temperature is 50°C, and the sealing treatment time is 10 minutes;

[0082] The sealing solution includes components with the following concentrations: 30wt.% metavanadate, 20wt.% aminosilane, 1wt.% nano-silica sol, 0.1wt.% citric acid, 0.1wt.% hexadecyltrimethylammonium bromide, 0.01wt.% vanadate, and the balance is water.

[0083] The element composition of the obtained chemical conversion film is: Mg: 26wt.%, Al: 3wt.%, V: 61wt.%, P: 5wt.%, Ca: 1wt.%, Si: 1wt.%, O: 3wt.%, and the remainder is impurities.

[0084] Figure 6 The macroscopic photograph of the surface of the magnesium alloy with a chemical conversion film prepared in Example 2 of the present invention after the salt spray test shows that there is filiform corrosion on the surface of the magnesium alloy.

[0085] Figure 7 From the macroscopic photograph of the surface of the magnesium alloy with the chemical conversion film prepared in Example 2 of the present invention after the salt spray test and standing for 12 hours, it can be seen that the filamentous corrosion on the surface disappears, proving that the chemical conversion film obtained in the present invention has a self-repairing function.

[0086] Example 3

[0087] The sample to be processed is a 20mm×10mm×5mm AZ91D magnesium alloy substrate, and its chemical composition is as follows by mass percentage: Al: 8.5-9.5%, Zn: 0.45-0.90%, Mn: 0.17-0.40%, Si≤0.050%, Cu≤0.025%, Ni≤0.01, Fe≤0.004, and the remainder is Mg and unavoidable impurities.

[0088] The specific steps of preparing a crack-free and self-healing surface chemical conversion film on the sample surface are:

[0089] 1) Pre-treatment

[0090] The magnesium alloy substrate of the sample to be processed was successively polished, alkali washed, pickled, bleached and deashed;

[0091] The samples were polished with metallographic sandpaper to No. 2000, then cleaned with acetone, washed with ultrapure water, and dried;

[0092] The alkali washing temperature is 80°C, the alkali washing time is 5 minutes, and the sample is cleaned with ultrapure water after alkali washing. The alkali washing ingredients used are: 10wt.% sodium hydroxide, 20wt.% sodium phosphate, 15wt.% sodium carbonate, and 0.1wt.% hexadecyltrimethylammonium bromide;

[0093] The pickling temperature is 50°C and the time is 1 min. After pickling, the sample is cleaned with ultrapure water. The composition of the pickling solution is: 30wt.% oxalic acid, 1wt.% lactic acid, 5wt.% citric acid, 1wt.% glycolic acid, 0.1wt.% sodium dodecyl sulfate, and the balance is water;

[0094] The bleaching and deashing temperature is 60°C and the time is 10 minutes. After bleaching and deashing, the sample is cleaned with ultrapure water. The bleaching and deashing solution comprises: 20wt.% sodium hydroxide, 30wt.% disodium ethylenediaminetetraacetic acid, 1wt.% sodium carbonate, 1wt.% triethanolamine, 0.01wt.% sodium dodecyl sulfate, and the balance is water.

[0095] 2) Passivation

[0096] The pre-treated magnesium alloy substrate was placed in a passivation solution for passivation treatment at a temperature of 30°C for 1 min. After passivation, the surface of the sample was cleaned with ultrapure water.

[0097] The passivation solution comprises: 10wt.% phosphoric acid, 20wt.% dihydrogen phosphate, 20.0wt.% calcium nitrate, 20.0wt.% metavanadate, 0.01wt.% succinic acid, 0.01wt.% sodium dodecyl sulfate, 1wt.% phosphate, and the balance is water;

[0098] 3) Closed treatment

[0099] The magnesium alloy substrate is placed in a sealing solution for sealing treatment, the sealing treatment temperature is 50°C, and the sealing treatment time is 10 minutes;

[0100] The sealing solution comprises components with the following concentrations: 10wt.% metavanadate, 30wt.% aminosilane, 20wt.% nano-silica sol, 1wt.% citric acid, 0.01wt.% hexadecyltrimethylammonium bromide, 0.1wt.% vanadate, and the balance is water.

[0101] The element composition of the obtained chemical conversion film is: Mg: 17wt.%, Al: 4wt.%, V: 65wt.%, P: 7wt.%, Ca: 2wt.%, Si: 2wt.%, O: 3wt.%, and the remainder is impurities.

[0102] Example 4

[0103] The sample to be processed is an AM60B magnesium alloy substrate of 20mm×10mm×5mm, and its chemical composition is as follows by mass percentage: Al: 5.5-6.4%, Zn: 0.30%, Mn: 0.24-0.60%, Si: 0.08%, Cu≤0.025%, Ni≤0.01, Fe≤0.004, and the remainder is Mg and unavoidable impurities.

[0104] The specific steps of preparing a crack-free and self-healing surface chemical conversion film on the sample surface are:

[0105] 1) Pre-treatment

[0106] The magnesium alloy substrate of the sample to be processed was successively polished, alkali washed, pickled, bleached and deashed;

[0107] The samples were polished with metallographic sandpaper to No. 2000, then cleaned with acetone, washed with ultrapure water, and dried;

[0108] The alkali washing temperature is 50°C, the alkali washing time is 20 minutes, and the sample is cleaned with ultrapure water after alkali washing. The alkali washing ingredients used are: 20wt.% sodium hydroxide, 15wt.% sodium phosphate, 5wt.% sodium carbonate, and 0.1wt.% hexadecyltrimethylammonium bromide;

[0109] The pickling temperature is 15°C and the time is 3 minutes. After pickling, the sample is cleaned with ultrapure water. The composition of the pickling solution is: 5wt.% oxalic acid, 10wt.% lactic acid, 5wt.% citric acid, 2wt.% glycolic acid, 0.1wt.% hexadecyltrimethylammonium bromide, and the balance is water;

[0110] The bleaching and deashing temperature is 80°C and the time is 3 minutes. After bleaching and deashing, the sample is cleaned with ultrapure water. The bleaching and deashing solution comprises: 10wt.% sodium hydroxide, 15wt.% disodium ethylenediaminetetraacetate, 25wt.% sodium carbonate, 5wt.% triethanolamine, 0.01wt.% hexadecyltrimethylammonium bromide, and the balance is water.

[0111] 2) Passivation

[0112] The pre-treated magnesium alloy substrate was placed in a passivation solution for passivation treatment at a temperature of 30°C for 1 min. After passivation, the surface of the sample was cleaned with ultrapure water.

[0113] The passivation solution comprises: 5wt.% phosphoric acid, 15wt.% dihydrogen phosphate, 1.0wt.% calcium nitrate, 25wt.% metavanadate, 0.1wt.% succinic acid, 0.01wt.% Triton, 1wt.% phosphine carboxylic acid, and the balance is water;

[0114] 3) Closed treatment

[0115] The magnesium alloy substrate is placed in a sealing solution for sealing treatment, the sealing treatment temperature is 50°C, and the sealing treatment time is 7 minutes;

[0116] The sealing solution comprises components with the following concentrations: 15wt.% metavanadate, 30wt.% aminosilane, 10wt.% nano-silica sol, 1wt.% succinic acid, 0.01wt.% Triton, 0.1wt.% vanadate, and the balance is water.

[0117] The element composition of the obtained chemical conversion film is: Mg: 14wt.%, Al: 2wt.%, V: 70wt.%, P: 5wt.%, Ca: 2wt.%, Si: 2wt.%, O: 3wt.%, and the remainder is impurities.

[0118] Example 5

[0119] The sample to be processed is a ZK60 magnesium alloy substrate of 20 mm×10 mm×5 mm, and its chemical composition is as follows by mass percentage: Zn: 4.8-6.2%, Zr: 0.50%, Mn: 0.24-0.6%, and the remainder is Mg and unavoidable impurities.

[0120] The specific steps of preparing a crack-free and self-healing surface chemical conversion film on the sample surface are:

[0121] 1) Pre-treatment

[0122] The magnesium alloy substrate of the sample to be processed was successively polished, alkali washed, pickled, bleached and deashed;

[0123] The samples were polished with metallographic sandpaper to No. 2000, then cleaned with acetone, washed with ultrapure water, and dried;

[0124] The alkali washing temperature is 70°C, the alkali washing time is 10 minutes, and the sample is cleaned with ultrapure water after alkali washing. The alkali washing ingredients used are: 13wt.% sodium hydroxide, 20wt.% sodium phosphate, 12wt.% sodium carbonate, and 0.1wt.% sodium dodecyl sulfate;

[0125] The pickling temperature is 45°C and the time is 1 min. After pickling, the sample is cleaned with ultrapure water. The composition of the pickling solution is: 5wt.% oxalic acid, 15wt.% lactic acid, 15wt.% citric acid, 3wt.% glycolic acid, 0.1wt.% sodium dodecyl sulfate, and the balance is water;

[0126] The bleaching and deashing temperature is 60°C and the time is 10 minutes. After bleaching and deashing, the sample is cleaned with ultrapure water. The bleaching and deashing solution comprises: 5wt.% sodium hydroxide, 30wt.% disodium ethylenediaminetetraacetic acid, 15wt.% sodium carbonate, 5wt.% triethanolamine, 0.01wt.% sodium dodecyl sulfate, and the balance is water.

[0127] 2) Passivation

[0128] The pre-treated magnesium alloy substrate was placed in a passivation solution for passivation treatment at a temperature of 30°C for 1 min. After passivation, the surface of the sample was cleaned with ultrapure water.

[0129] The passivation solution comprises: 7wt.% phosphoric acid, 12wt.% dihydrogen phosphate, 2wt.% calcium nitrate, 30wt.% metavanadate, 0.1wt.% citric acid, 0.01wt.% sodium dodecyl sulfate, 0.5wt.% vanadate, and the balance is water;

[0130] 3) Closed treatment

[0131] The magnesium alloy substrate is placed in a sealing solution for sealing treatment, the sealing treatment temperature is 50°C, and the sealing treatment time is 7 minutes;

[0132] The sealing solution includes components with the following concentrations: 18 wt.% metavanadate, 15 wt.% aminosilane, 15 wt.% nano silica sol, 0.5 wt.% citric acid, 0.5 wt.% hexadecyltrimethylammonium bromide, 0.5 wt.% phosphonate, and the balance is water.

[0133] The element composition of the obtained chemical conversion film is: Mg: 16wt.%, V: 69wt.%, P: 7wt.%, Ca: 1wt.%, Si: 2wt.%, O: 4wt.%, and the remainder is impurities.

[0134] Comparative Example 1

[0135] The preparation method of this comparative example is the same as that of Example 1, except that the sealing treatment in step (7) is not performed.

[0136] The chemical conversion film layer prepared in this comparative example has the following element contents: Mg: 31wt.%, Al: 6wt.%, V: 52wt.%, P: 5wt.%, Ca: 3wt.%, O: 3wt.%, and the remainder is impurities.

[0137] The surface microscopic morphology of the chemical conversion film obtained in this comparative example is shown in FIG. Figure 4 As shown, there are a large number of microcracks distributed on the surface.

[0138] The chemical conversion film of Example 1 was subjected to a 100-hour neutral salt spray scratch test. Figure 5 This is a photo of the appearance after a 100-hour neutral salt spray test. It can be seen that corrosion spots appear near the scratches.

[0139] Comparative Example 2

[0140] The preparation method of this comparative example is the same as that of Example 1, except that in step (7), no metavanadate is added to the passivation solution and the sealing solution.

[0141] The chemical conversion film layer prepared in this comparative example has the following element contents: Mg: 29wt.%, Al: 5wt.%, V: 50wt.%, P: 5wt.%, Ca: 3wt.%, Si: 2wt.%, O: 6wt.%, and the remainder is impurities.

[0142] The film layer obtained in this comparative example has a large number of microcracks distributed on the surface of the film layer.

[0143] Comparative Example 3

[0144] The preparation method of this comparative example is the same as that of Example 2, except that the sealing solution of 10-20 g / L aluminum sulfate and 10-30 g / L sodium hydroxide of "A magnesium alloy surface sealing solution and sealing process thereof" of Chinese Patent Publication No. CN101096762A is used for sealing treatment.

[0145] The chemical conversion film layer prepared in this comparative example includes the following contents of the constituent elements: Mg: 29wt.%; Al: 12wt.%; V: 27wt.%; P: 13wt.%; Ca: 3wt.%; O: 16wt.%; the remainder is impurities.

[0146] The film layer obtained in this comparative example has a large number of microcracks on the surface of the film layer and has poor corrosion resistance and no self-repairing property.

Claims

1. A crack-free and self-repairing magnesium alloy surface chemical conversion film, the components of which are as follows by weight: Mg: 10.0-30.0%, Al: 0-5%, V: 60-75%, P: 1-7%, Ca: 1-3%, Si: 1-2%, O: 1-5%, and the remainder is impurities.

2. The method for preparing a crack-free and self-repairing magnesium alloy surface chemical conversion film as claimed in claim 1, characterized in that: The following steps are involved: 1) Pre-treatment The magnesium alloy substrate is successively polished, alkali washed, pickled, bleached and deashed; 2) Passivation The pre-treated magnesium alloy substrate is placed in a passivation solution for passivation treatment at a temperature of 15 to 40°C for a passivation treatment time of 0.5 to 3 minutes; The passivation solution comprises the following components: 1.0-10.0wt.% phosphoric acid, 1.0-40.0wt.% dihydrogen phosphate, 1.0-20.0wt.% calcium nitrate, 5.0-30.0wt.% metavanadate, 0.01-1wt.% complexing agent, 0.01-1wt.% surfactant, 0.01-1wt.% corrosion inhibitor, and the balance is water; 3) Closed treatment The magnesium alloy substrate is placed in a sealing solution for sealing treatment, the sealing treatment temperature is 50 to 90° C., and the sealing treatment time is 0.5 to 10 minutes; The sealing solution comprises the following components: 10.0-30.0 wt.% metavanadate, 1.0-30.0wt.% aminosilane, 1.0-20.0wt.% nano silica sol, 0.01-1wt.% complexing agent, 0.01-1wt.% surfactant, 0.01-1wt.% corrosion inhibitor, and the balance is water.

3. The preparation method according to claim 2, characterized in that: In step 1), the alkali washing temperature is 50-80° C., and the alkali washing time is 5-20 min; preferably, the alkali washing solution comprises: 1.0-20.0 wt. % of sodium hydroxide, 1.0-20.0 wt. % of sodium phosphate, 1.0-30.0 wt. % of sodium carbonate, 0.01-1 wt. % of a surfactant, and the balance is water.

4. The preparation method according to claim 2, characterized in that: In step 1), the pickling temperature is 15-70° C., and the pickling time is 0.5-3 min; preferably, the pickling solution comprises: 1.0-30.0 wt. % oxalic acid, 1.0-30.0 wt. % lactic acid, 1.0-30.0 wt. % citric acid, 1.0-30 wt. % glycolic acid, 0.01-1 wt. % surfactant, and the balance is water.

5. The preparation method according to claim 2, characterized in that: In step 1), the bleaching and deashing temperature is 60-90° C., and the bleaching and deashing time is 0.5-10 min; preferably, the solution used for bleaching and deashing comprises 1.0-20.0 wt.% of sodium hydroxide, 1.0-30.0 wt.% of disodium ethylenediaminetetraacetate, 1.0-30.0 wt.% of sodium carbonate, 1-10.0 wt.% of triethanolamine, 0.01-1 wt.% of a surfactant, and the balance is water.

6. The preparation method according to claim 2, 3, 4 or 5, characterized in that: The surfactant is an anionic surfactant, a cationic surfactant, a zwitterionic surfactant or a nonionic surfactant.

7. The preparation method according to claim 2, characterized in that: The complexing agent is one or more of citric acid, succinic acid, EDTA and ethylenediamine.

8. The preparation method according to claim 2, characterized in that: The corrosion inhibitor is one or more of anodic corrosion inhibitor vanadate, cathodic corrosion inhibitor phosphate, organic corrosion inhibitor phosphine carboxylic acid, phosphonate and the like.

9. The preparation method according to any one of claims 2 to 8, characterized in that: After the grinding, alkali washing, pickling, bleaching and deashing, and passivation steps, the magnesium alloy substrate is rinsed with deionized water for 1 to 2 times.

10. A self-repairing passivation solution for magnesium alloy surface treatment, characterized in that: The invention comprises the following components: 1.0-10.0wt% phosphoric acid, 1.0-40.0wt% dihydrogen phosphate, 1.0-20.0wt% calcium nitrate, 5.0-30.0wt% metavanadate, 0.01-1wt% complexing agent, 0.01-1wt% surfactant, 0.01-1wt% corrosion inhibitor, and the balance is water.

11. A self-repairing sealing solution for magnesium alloy surface treatment, characterized in that: The invention comprises the following components: 10.0-30.0wt% of metavanadate, 1.0-30.0wt% of aminosilane, 1.0-20.0wt% of nano silica sol, 0.01-1wt% of complexing agent, 0.01-1wt% of surfactant, 0.01-1wt% of corrosion inhibitor, and the balance is water.

Citation Information

Patent Citations

  • Magnesium alloy surface hole sealing solution and hole sealing process

    CN101096762A

  • Self-healing coating formed on magnesium alloy surface and method for forming self-healing coating

    CN108300255B

  • Film formation solution of chromium- and crack-free magnesium alloy conversion film and film layer preparation method

    CN109402621A

  • Preparation method of phosphate-based corrosion-resistant self-healing coating on magnesium alloy surface

    CN109680318B

  • Preparation method of corrosion-resistant self-healing coating on magnesium alloy surface based on calcium salt

    CN109680319B